Anatomical, Chemical and Antimicrobial Activity of Pistacia lentiscus L. - Kinel, Gizem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The genus Pistacia L. is a member of the family Anacardiaceae and consists of 10 accepted species. According to monograph of Zohary published on 1952, the genus is divided into 4 sections and 11 species included. In Northern Cyprus 4 Pistacia species occur, wild ones: P. atlantica Desf. , P. lentiscus L., P. terebinthus L., and cultivated one P. vera L.. The male trees use for to extract resin and female trees produce red drupe fruits which is use to make traditional hard biscuits at patisseries. Pistacia lentiscus is an evergreen shrub or small dioecious tree. Leaves are paripinnate with strong resin odour. Leaflets 6 or 8 pairs are elliptical, apex and base acute, margin entire. At spring-summer seasons it gives white flowers. It is multi trunked plant with many branches and generally resists to breakage. In this study leaf anatomical characteristics and antimicrobial effect of its fruit have been check with methanol (CH3OH), chloroform (CHCl3), dichloromethane (CH2Cl2), acetone (CH3COCH3), hexane (C6H14), ethanol (C2H5OH) and distilled water (H2O) extracts against gram positive and gram negative bacteria such as; E. coli ,K. pneumoniae S aureus and E. faecalis, was investigated. All examined specimens collected from wild population in Karpaz region. The cross section of the leaflets made by hand, it is observed that on both surface q single layer of thin walled epidermal cells, covered by thick layer cuticula. Leaves are dorsiventral (bifacial) adaxial palisade consists of one layer, and the abaxial the abaxial spongy parnchima consists of several layers and the cell wall are very similar in appearance. Stoma only occurs on upper surface, no hairs. MIC of all chemicals extracts is investigated to be 128 mg/L. Keywords: Pistacia lentiscus, anatomical structure of seeds, antibacterial activity.

ÖZ:Pistacia L. cinsi, Anacardiaceae familyasının bir üyesidir ve son literatüre göre 10 kabul edilen türden oluşmaktadir. 1952'de yayınlanan Zohary'nin monografisine göre, cins olarak 4 seksiyona ayrılmıştır ve 11 türe vardır.. Kuzey Kibris’ta 4 Pistacia türü bulunmaktadır, yabani olanlar P.atlantica Desf., P. lentiscus L., P. terebinthus L., ve yetiştirilen tek tür P. vera L. Erkek ağaçlardan recine elde edilmekte ve dişi ağaçlar kırmızı sert meyveleri Kıbrıs'ta pastanelerde geleneksel olarak peksemet (sert bisküvi) yapımında kullanılmaktadır. Pistacia lentiscus, yaprak dökmeyen bir çalı veya küçük bir ağaçtır. Yapraklar paripennattır ve güçlü reçine kokusuna sahiptir. Yaprakçıklar 6 veya 8 eliptik, akut, kenarları tam olayaprakçıktan oluşur. İlkbahar-yaz mevsiminde beyaz çiçekler açmaktadır. Çok gövdeli ve çok dallı bir bitkidir, genellikle kırılmaya karşı dayanıklıdır. Pistacia türlerinde az sayıda anatomik çalışma yayınlanmıştır. Bu çalışmada, Karpaz yöresinden doğal ortamından toplanan örneklerin yapraklarının anatomik özellikleri ve meyvelerinin antibakteriyel aktivitesi metanol, kloroform, diklorometan, aseton, heksan, ethanol ve su ekstrelerinin gram positive ve gram negative microrganismalarinin ki bunlar; S. aureus, E. faecalis, E. coli ve K. pneumoniae üzerindeki etkisi incelendi. Bitkinin yaprak kesitleri el ile alınmıştır, microskope incelemesi sonucunda yaprağın her iki yüzeyinde de ince tek tabaka halinde epiderma hücreleri, kutiküla kalın, yapraklar dorsiventral tiptedir, üstte palizat parenkiması, alt yüzde ise sünger parenkiması yer alır. Palizat parenkiması tek sıra hücreden oluşmaktadır. Sünger parenkiması ise birbirine benzeyen çok sıralı hücreden meydana gelmiştir. Stomalar sadece üst yüzeyde bulunur ve yapraklarda tüy gözlenmemiştir. Meyvenin minimum inhibitör konsantrasyonunun 128 mg/L'den olduğu metanol, kloroform,diklorometan, aseton, heksan, ethanol ve su ekstrelerini kullanarak yapilan deneylerde belirlenmiştir. Anahtar Kelimeler: Pistacia lentiscus, meyvesinin anatomikal yapısı, antibakteriyal aktivitesi.
Master of Science in Chemistry. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2019. Co-Supervisor: Prof. Dr. Fatma Neriman Özhatay and Supervisor. Prof. Dr. Mustafa Gazi.
Keywords: Aromatic Plants; Medicinal Plants; Antioxidants-Health aspects; Pistacia lentiscus; anatomical structure of seeds; antibacterial activity